Rapid, synchronous, and stable induction of type 1 piliation in Escherichia coli by using a chromosomal lacUV5 promoter. - Woodall, L D (1993)
Type 1 pili are filamentous proteinaceous appendages produced by certain members of the family Enterobacteriaceae. In Escherichia coli, the adhesive properties of these pili are due to the binding of at least one minor pilus component to mannose, a sugar common to cell surface molecules of many eukaryotic cells. The study of pilus assembly may be benefited by a rapid way of inducing pilus synthesis de novo. We describe herein the construction and characterization of a strain in which piliation can be rapidly induced by the addition of lactose or its analog isopropyl-beta-D-thiogalactopyranoside. This was accomplished by placing the chromosomal fimA gene (encoding the major structural subunit of pili) under lacUV5 promoter control. Further experiments suggested that transcription of genes downstream of fimA, whose products are required for normal pilus assembly and function, may also be controlled by the lacUV5 promoter. The construction described herein may have a variety of applications apart from aiding the study of pilus assembly since its adhesive properties can be rapidly and easily turned on and off.